Retrotransposons in Deschampsia antarctica E. Desv. (Poaceae) genome: Diversity, abundance and chromosomal distribution - Topalian, Juliana; González, María Laura; Chiapella, Jorge Oscar; Urdampilleta, Juan Domingo (Polar Science)
Deschampsia antarctica is one of the two native vascular plants present in the Antarctic continent. More than half of its genome is composed of repetitive DNA. The present work aims to study the amount, composition and chromosomal localization of the main retroelements in the genome of D. antarctica, via a bioinformatic analysis and cytogenetic approach in two Antarctic localities. The retroelements are the largest fraction of genomic repetitive DNA. Ty3-Gypsy superfamily was more abundant than Ty1-Copia in D. antarctica's genome. However, Ty1-Copia was more diverse. Angela, SIRE, TatV and Tekay families were the most abundant in the studied genome. The hybridization signals showed that the four retrotransposon families have dispersal distributions in both Antarctic localities studied. However, some differences in the chromosomal distribution were observed among families and between localities. This study contributes to the understanding of the diversity and distribution of repetitive DNA in D. antarctica. Fil: Topalian, Juliana. Instituto Nacional de Tecnología Agropecuaria. Centro de Investigación en Ciencias Veterinarias y Agronómicas. Instituto de Agrobiotecnología y Biología Molecular. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Agrobiotecnología y Biología Molecular; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina Fil: González, María Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina Fil: Chiapella, ...